Macrophage depletion in inflamed rat knees prevents the activation of synovial mesenchymal stem cells by weakening Nampt and Spp1 signaling - Hayato Kodama; Kentaro Endo; Ichiro Sekiya (BMC, 2024)
Abstract Background Macrophages and mesenchymal stem cells (MSCs) engage in crucial interplay during inflammation and have significant roles in tissue regeneration. Synovial MSCs, as key players in joint regeneration, are known to proliferate together with macrophages in synovitis. However, the crosstalk between synovial MSCs and macrophages remains unclear. In this study, we investigated changes in the activation of synovial MSCs in inflamed rat knees following selective depletion of macrophages with clodronate liposomes. Methods Acute inflammation was induced in rat knee joints by injection of carrageenan (day 0). Clodronate liposomes were administered intra-articularly on days 1 and 4 to deplete macrophages, with empty liposomes as a control. Knee joints were collected on day 7 for evaluation by histology, flow cytometry, and colony-forming assays. Concurrently, synovial MSCs were cultured and subjected to proliferation assays, flow cytometry, and chondrogenesis assessments. We also analyzed their crosstalk using single-cell RNA sequencing (scRNA-seq). Results Clodronate liposome treatment significantly reduced CD68-positive macrophage numbers and suppressed synovitis. Immunohistochemistry and flow cytometry showed decreased expression of CD68 (a macrophage marker) and CD44 and CD271 (MSC markers) in the clodronate group, while CD73 expression remained unchanged. The number of colony-forming cells per 1000 nucleated cells and per gram of synovium was significantly lower in the clodronate group than in the control group. Cultured synovial MSCs from both groups showed comparable proliferation, surface antigen expression, and chondrogenic capacity. scRNA-seq identified seven distinct synovial fibroblast (SF) subsets, with a notable decrease in the Mki67+ SF subset, corresponding to synovial MSCs, in the clodronate group. Clodronate treatment downregulated genes related to extracellular matrix organization and anabolic pathways in Mki67+ SF. Cell-cell communication analysis revealed diminished Nampt and Spp1 signaling interaction between macrophages and Mki67+ SF and diminished Ccl7, Spp1, and Csf1 signaling interaction between Mki67+ SF and macrophages in the clodronate group. Spp1 and Nampt promoted the proliferation and/or chondrogenesis of synovial MSCs. Conclusions Macrophage depletion with clodronate liposomes suppressed synovitis and reduced the number and activity of synovial MSCs, highlighting the significance of macrophage-derived Nampt and Spp1 signals in synovial MSC activation. These findings offer potential therapeutic strategies to promote joint tissue regeneration by enhancing beneficial signals between macrophages and synovial MSCs.